Study of dynamic of chicken infectious anaemia virus infection: which sample is more reliable for viral detection?. Issue 5 (3rd September 2018) - Vagnozzi, Ariel E.; Espinosa, Rodrigo; Cheng, Sunny; Brinson, Denise; O'Kane, Peter; Wilson, Jeanna; Zavala, Guillermo
ABSTRACT: Chicken infectious anaemia virus (CIAV) is a widely distributed immunosuppressive agent. SPF flocks and eggs used for vaccine production and diagnostics must be CIAV-free. Detection of CIAV infection in SPF flocks involves primarily serology or other invasive methods. In order to evaluate different types of samples for rapid detection of CIAV infection, a trial was conducted in serologically negative broiler breeder pullets vaccinated with a commercial live-attenuated CIAV vaccine. Controls and vaccinated groups were sampled before and after vaccination. Invasive and non-invasive samples were used for CIAV DNA detection by real-time PCR. Seroconversion occurred at 14 days post-inoculation (DPI) in the vaccinated group, whereas CIAV genome was detected by qPCR at 7 DPI in both invasive and non-invasive samples. Only invasive samples remained qPCR positive for CIAV DNA by 21 DPI despite seroconversion of the chickens.